2012
DOI: 10.2133/dmpk.dmpk-11-rg-126
|View full text |Cite
|
Sign up to set email alerts
|

Lower Expression of HNF4α and PGC1α Might Impair Rifampicin-mediated CYP3A4 Induction under Conditions Where PXR Is Overexpressed in Human Fetal Liver Cells

Abstract: Pregnane X receptor (PXR) mRNA was detected in HepG2 cells by RT-PCR, but not in human fetal liver (HFL) cells. CYP3A4 was induced by rifampicin (RIF), mifepristone (RU486), clotrimazole (CTZ), and dexamethasone (DEX) in HepG2 cells, while these PXR ligands with the exception of DEX did not induce CYP3A4 mRNA expression in HFL cells. Ad-PXR infection increased mRNA levels of PXR and CYP3A4 in both cells despite the absence of PXR ligands. Similar results were observed in reporter gene assays. However, in HFL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies showed that full activation of PXR under RIF induction was dependent on the coregulation of RXRα, HNF4α, SRC-1, and PGC-1α . Thus, we assessed the coregulation of these coactivators by PXR on CYP3A4 promoter activity in the presence of RIF and OA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that full activation of PXR under RIF induction was dependent on the coregulation of RXRα, HNF4α, SRC-1, and PGC-1α . Thus, we assessed the coregulation of these coactivators by PXR on CYP3A4 promoter activity in the presence of RIF and OA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that full activation of PXR under RIF induction was dependent on the coregulation of RXRα, HNF4α, SRC-1, and PGC-1α. 26 Thus, we assessed the coregulation of these coactivators by PXR on CYP3A4 promoter activity in the presence of RIF and OA. Full-length human RXRα, HNF4α, SRC-1, and PGC-1α expression constructs were cotransfected with human PXR/vector control and CYP3A4 promoter constructs into HepG2 cells.…”
Section: Effects Of Oa On Pxr Transactivation Of Cyp3a4mentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA was used to carry out real-time polymerase chain reaction (PCR) using SYBR ® Premix ExTaq (TaKaRa Bio) in order to measure mRNA levels of CYP3A4 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). The amplification reactions were performed with specific primers for CYP3A4 (forward: 5'-CTGTGTTTCCAAGAGAAGTTAC-3' and reverse: TGCATCAATTTCCTCCTGCAG-3'), and GAPDH (forward: 5'-CATGGGTGTGAACCATGAGAA-3' and reverse: 5'-GGTCATGAGTCCTTCCACGAT-3') (19). Quantitative values were obtained above the threshold PCR cycle number (Ct) at which the increase in signal associated with an exponential growth in PCR products was detected using Thermal Cycler Dice TM TP800 (TaKaRa Bio).…”
Section: Quantitative Analysis Of Cyp3a4 Mrna Contentsmentioning
confidence: 99%
“…Activators of PXR, which include some anticancer drugs, induce a conformational change resulting in dissociation of corepressors and recruitment of coactivators [ 19 ]. Coactivators that have been identified include steroid receptor coactivators (SRCs) 1, 2 and 3, peroxisome proliferator activated receptor gamma coactivator 1-alpha (PGC-1α), forkhead box O 1 transcription factor (FOXO1), protein arginine methyltransferase (PRMT) and p300 [ 2 , 29 , 30 ]. Thus, activity of PXR can be influenced by a number of factors including and excluding direct activators or inhibitors.…”
Section: Introductionmentioning
confidence: 99%